2015
DOI: 10.1007/s12161-015-0252-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sample Preparation Methods for the Determination of Ca, Cu, Fe, K, and Na in Milk Powder Samples by ICP-OES

Abstract: In this paper, a comparative study between three acid decomposition procedures of milk powder samples for the determination of Ca, Cu, Fe, K, and Na by optical emission spectrometry with inductively coupled plasma is presented. Utilizing a reflux system, it was possible to increase the temperature of the digester block above the boiling point of the reaction medium, avoiding the loss of analyte and the excessive evaporation of the acids during the heating. Conditions of acidity (10 mL HNO 3 /H 2 SO 4 ), temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 30 publications
1
4
0
3
Order By: Relevance
“…26 The variable H 2 SO 4 volume was not significant, however, in the preliminary tests it was observed that the decomposition carried out with mixture of acids (HNO 3 and H 2 SO 4 ) has better analytical signals in the determination of the four elements compared with the use of only HNO 3 . The same was verified by Oreste et al 17 by using the mixture in order to determine Ca, Cu, Fe, K and Na milk powder samples.…”
Section: Experimental Designsupporting
confidence: 61%
See 1 more Smart Citation
“…26 The variable H 2 SO 4 volume was not significant, however, in the preliminary tests it was observed that the decomposition carried out with mixture of acids (HNO 3 and H 2 SO 4 ) has better analytical signals in the determination of the four elements compared with the use of only HNO 3 . The same was verified by Oreste et al 17 by using the mixture in order to determine Ca, Cu, Fe, K and Na milk powder samples.…”
Section: Experimental Designsupporting
confidence: 61%
“…Its applicability has been shown in the preparation of different types of matrices for subsequent determination of metals by different analytical techniques. [16][17][18] Another simple and efficient alternative used for the preparation of organic samples employs solubilization with tetramethylammonium hydroxide (TMAH). Samples treated with TMAH provides a solution with characteristics similar to a suspension, with a low dilution factor and remaining stable for months at room temperature.…”
Section: -13mentioning
confidence: 99%
“…The cold finger is inserted into a digestion vessel for sample preparation, using an open system with conventional heating. Our research group has applied a new design of cold finger for sample preparation with a reflux system, which has demonstrated a high efficiency in decomposing different samples, as can be observed in the published papers on the determination of Hg in biological samples; 33 Cd, Pb and Sn in meat; 34 Ca, Cu, Fe, K and Na in milk powder; 35 As, Cd, Pb, and Se in rice 36 and Al, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Pb and Zn in yerba mate. 37 Thus, this study aims to determine the concentrations of Cu, Zn, Cr and Pb in different species of fish from estuarine and limnic portions of the São Gonçalo channel, in different seasons of 2013 and 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This solution is preferred over open systems offering reduced risk of analyte loss. Sample preparation through such device was adopted to determine calcium and other minerals in milk powders and MIF (n = 4) by inductively coupled plasma optical emission spectrometry (ICP-OES) (Oreste, de Souza, Pereira, Lisboa, Cidade et al, 2016). Results fitted well (at 99% confidence level) with those obtained by conventional open-vessel heating system.…”
mentioning
confidence: 76%